Etyka biznesu a społeczna odpowiedzialność biznesu - Jastrzębska, Ewa (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2010)
This study analyzes the philosophical roots of business ethics and assesses this fields influence on the birth of corporate social responsibility. Business ethics have done more than lay the foundations for CSR: Numerous highly publicized corporate scandals evoking discussions on such ethics, have proved that institutionalization of business ethics has become increasingly necessary. Firstly, it would allow creation of stable foundations for enterprises to act responsibly. Secondly, it would improve the image of business activity in the eyes of society as well as positively influence the efficiency of such activity.